Effects of Static versus Ballistic Stretching on Hamstring: Quadriceps Strength Ratio and Jump Performance in Ballet Dancers and Resistance Trained Women. Issue 3 (September 2018) - Lima, Camila D.; Brown, Lee E.; Ruas, Cassio V.; Behm, David G.
Stretching, while enhancing joint flexibility, may also decrease the hamstring:quadriceps (H:Q) strength ratio, which is used to identify knee strength imbalances and lower extremity muscle and ligament injury risk in the practice of sports and other physical activities. Stretching may also decrease muscle force and jump performance. However, these effects may depend on the population in question and mode of stretching. The purpose of this study was to compare the effects of static stretching (SS) and ballistic stretching (BS) on concentric H:Q ratio, squat jump (SJ) and countermovement jump (CMJ) height, and SJ:CMJ ratio between ballet dancers and resistance trained women. Fifteen resistance trained women and 12 ballet dancers were tested over five sessions. The first visit consisted of demographic measurements and instruction in testing protocols (no stretching), while the other four involved SS or BS in a counterbalanced order. At each of these sessions, six stretching exercises were performed, three focusing on quadriceps and three on hamstrings, in counterbalanced order. Two way repeated measures ANOVAs were used to compare interactions between conditions and groups for H:Q and SJ:CMJ ratios. Both groups demonstrated a significant decrease in H:Q ratio after SS, but there were no significant differences in SJ:CMJ ratio or jump height between conditions (p > 0.001). However, the ballet group had greater SJ:CMJ ratios and SJ heights than the resistance trained group. These findings suggest that both ballet dancers and resistance trained women decrease H:Q ratio similarly after BS and SS. Long-duration stretching negatively impacts H:Q ratio in the short term, which may lead to greater hamstring to quadriceps imbalance regardless of training background.